γ-Tubulin 2 Nucleates Microtubules and Is Downregulated in Mouse Early Embryogenesis - Vinopal, Stanislav; Černohorská, Markéta; Sulimenko, Vadym; Sulimenko, Tetyana; Vosecká, Věra; Flemr, Matyáš; Dráberová, Eduarda; Dráber, Pavel (PLOS ONE, 2012)
γ-Tubulin is the key protein for microtubule nucleation. Duplication of the γ-tubulin gene occurred several times during evolution, and in mammals γ-tubulin genes encode proteins which share ∼97% sequence identity. Previous analysis of Tubg1 and Tubg2 knock-out mice has suggested that γ-tubulins are not functionally equivalent. Tubg1 knock-out mice died at the blastocyst stage, whereas Tubg2 knock-out mice developed normally and were fertile. It was proposed that γ-tubulin 1 represents ubiquitous γ-tubulin, while γ-tubulin 2 may have some specific functions and cannot substitute for γ-tubulin 1 deficiency in blastocysts. The molecular basis of the suggested functional difference between γ-tubulins remains unknown. Here we show that exogenous γ-tubulin 2 is targeted to centrosomes and interacts with γ-tubulin complex proteins 2 and 4. Depletion of γ-tubulin 1 by RNAi in U2OS cells causes impaired microtubule nucleation and metaphase arrest. Wild-type phenotype in γ-tubulin 1-depleted cells is restored by expression of exogenous mouse or human γ-tubulin 2. Further, we show at both mRNA and protein levels using RT-qPCR and 2D-PAGE, respectively, that in contrast to Tubg1, the Tubg2 expression is dramatically reduced in mouse blastocysts. This indicates that γ-tubulin 2 cannot rescue γ-tubulin 1 deficiency in knock-out blastocysts, owing to its very low amount. The combined data suggest that γ-tubulin 2 is able to nucleate microtubules and substitute for γ-tubulin 1. We propose that mammalian γ-tubulins are functionally redundant with respect to the nucleation activity.